The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/polym11020245
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Roll-to-Roll Printed Air-Gap Touch Sensors

Abstract: Although printed electronics technology has been recently employed in the production of various devices, its use for the fabrication of electronic devices with air-gap structures remains challenging. This paper presents a productive roll-to-roll printed electronics method for the fabrication of capacitive touch sensors with air-gap structures. Each layer of the sensor was fabricated by printing or coating. The bottom electrode, and the dielectric and sacrificial layers were roll-to-roll slot-die coated on a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…It can be a simple parallel plate capacitor or integrated into an FET device as the gate capacitor. [ 47,65–68 ] The pressure sensitivity of a capacitive pressure sensor can be defined as: SC=δΔCC0/δp where C and C 0 are the capacitances with and without applied pressure, Δ C = C − C 0 , and p is the applied pressure. It is usually not constant and tends to decrease with large increases in pressure.…”
Section: Mechanical Sensorsmentioning
confidence: 99%
“…It can be a simple parallel plate capacitor or integrated into an FET device as the gate capacitor. [ 47,65–68 ] The pressure sensitivity of a capacitive pressure sensor can be defined as: SC=δΔCC0/δp where C and C 0 are the capacitances with and without applied pressure, Δ C = C − C 0 , and p is the applied pressure. It is usually not constant and tends to decrease with large increases in pressure.…”
Section: Mechanical Sensorsmentioning
confidence: 99%
“…Since the electrical performance of our acceleration sensors is affected greatly by the air gap thickness, reducing the size of sensor samples is desired highly. In fact, the sensor samples made in this study are about 75% of our previous bridge type air gap-based touch sensors [55].…”
Section: Electrical Characteristics Of the Sensor Samplesmentioning
confidence: 99%
“…Some examples are motion sensors [52], touch sensors [53] and switching devices. [54] An air gap-based bridge type touch sensor was fabricated and reported by the authors [55], but studies on the fabrication of air gap acceleration sensors have not been reported and fabrication of air gap-based electronic devices using the productive roll-to-roll process has not been conducted either. The roll-to-roll printing process is difficult to optimize compared to the sheet-to-sheet approach using ordinary printing processes including screen printing, inkjet printing, and spin coating.…”
Section: Introductionmentioning
confidence: 99%
“…It is found from our previous reports that poly(vinyl alcohol) (PVA) is more suitable for the sacrificial layer than those three materials in Table 1. 43,45 Since PVA is the representative water-soluble material, 46 As for fabrication processes of air-gap-structured electronic devices, inkjet printing and screen printing have been often used in printed electronics, 42−44 but roll-to-roll processes are considered more productive. 47−49 Printing/coating and curing are executed continuously during the roll-to-roll process, as the flexible substrate moves from the unwinder to the rewinder (Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…This study aims at developing a roll-to-roll printed electronics technology for fabricating air-gap-based flexible sensors without relying on the MEMS process. The authors' previous work 45 presents bridge-structured touch sensors with an air-gap, but the sensitivity of 0.0026%/kPa needs a significant improvement. Herein, a new design with a smaller size and a cantilever structure is proposed.…”
Section: ■ Introductionmentioning
confidence: 99%